The Maternal Role On Emotional Competence Development of Early Childhood - Yustina Yettie (Universitas Ahmad Dahlan, 2019)
AbstractEmotional competence is a multi-dimensional construct, consists of the skills to recognize and understand emotions, express emotions appropriately, and regulate emotions. Emotional competence develops very rapidly during preschool age and helps the child's success in fulfilling the developmental task of that age, such as building a positive relationship with the social environment, regulating emotion in social interaction, as well as learning skills such as concentrating and following the teacher's direction. A number of studies also proved emotional competence as the predictor of social competence and academic competence of children. This article aims to discuss the theoretical review and research review on the maternal role in the development of children's emotional competence. It was found that mother has a protective factor through attachment and emotional socialization. Secure attachment helps the child to regulate negative emotions. Conversely, insecure attachment results in inadequate emotional regulation skills. Through the socialization of emotions by the mother, children learn to recognize emotions, express emotions, and regulate emotions. The maternal role is also related with cultural frames. Suggestions are given for further research on conceptual definition, instruments, and interventions to optimize the emotional competence of early childhood.Keywords: attachment, emotional socialization, emotional competence, early childhood